Traditional and electronic poster in conference presentation / Nor Hafizah Rosli - Rosli, Nor Hafizah (Faculty of Art and Design, Universiti Teknologi MARA Melaka, Alor Gajah Campus, 2014)
The usage of poster in conferences had been arise The poster sessions often attract mixed analysis due to their physical constraints and because they are considered less impressive than paper sessions (Swales &Feak 2000; Swales 2004). However, posters do play an significant part in conferences, enabling academics to display not only their completed research work, but also the most interestingly ongoing research and preliminary findings that would not be post in a paper session. This makes poster session an interesting, engaging event for participants and a valid alternative to other, more sophisticated genres.